2012
DOI: 10.1111/j.1469-0691.2012.03936.x
|View full text |Cite
|
Sign up to set email alerts
|

Can infants be protected by means of maternal vaccination?

Abstract: The administration of vaccines is not usually recommended in pregnant women because of a fear of severe adverse events for the fetus. However, contraindication to vaccination applies only to vaccines based on live attenuated viruses for the theoretical possibility that they might infect the fetus. In contrast, the use of several inactivated vaccines is useful and recommended. As a result of the transplacental passage of antibodies, maternal immunization can reduce the risk of vaccine-preventable diseases that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 63 publications
(94 reference statements)
1
23
0
1
Order By: Relevance
“…We have previously demonstrated that maternal immunization may represent an alternative strategy for protecting the neonate against pertussis (44). However, so far the focus of maternal immunization studies has been on the induction of antibodies (14). Here, in addition to maternal antibodies, we further examined the role of maternal cytokines following immunization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that maternal immunization may represent an alternative strategy for protecting the neonate against pertussis (44). However, so far the focus of maternal immunization studies has been on the induction of antibodies (14). Here, in addition to maternal antibodies, we further examined the role of maternal cytokines following immunization.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination with TT induces a specific antibody response that is transported across the placenta with 100% efficiency and provides protection against neonatal tetanus (12,13). In addition, vaccinations against Haemophilus influenzae type b and pneumococcal infections are other examples of success in maternal immunization strategies (14).…”
mentioning
confidence: 99%
“…La vacunación de las mujeres gestantes es actualmente una forma de prevención de una amplia variedad de enfermedades como el tétanos, tos ferina, difteria, infecciones por neumococo, meningococo, rotavirus, virus del papiloma humano, Haemophilus influenzae tipo b y el herpes zóster (37,38). Sin embargo, en cuanto al SGB, el beneficio de una vacuna comparado con la profilaxis con antibióticos sería que podría prevenir la infección de inicio tardío y no conlleva el riesgo de aumentar la resistencia bacteriana.…”
Section: Vacunaciónunclassified
“…123 Multiple vaccines were examined with regards to their appropriateness for maternal vaccination, including the influenza, pneumococcal, dTp, HPV, MMR, V, meningococcal, HAV and HBV vaccines. Of these vaccines, LAIV, MMR, and V are contraindicated for pregnant women, whereas HPV is not recommended for pregnant women.…”
Section: Vaccination Of Pregnant Womenmentioning
confidence: 99%